2010
DOI: 10.1007/s10620-010-1462-4
|View full text |Cite
|
Sign up to set email alerts
|

Pringle Maneuver Deteriorates Gut Barrier Dysfunction Induced by Extended-Liver Radiofrequency Ablation

Abstract: The application of the Pringle maneuver concurrently with extended liver RFA aggravates gut barrier dysfunction with more aggressive translocation of endotoxins and intestinal bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…However, Pringle´s maneuver does not only affect the liver as described above but also causes systemic changes as shown by Ypsilantis et al [27][28][29].…”
Section: Discussionmentioning
confidence: 94%
“…However, Pringle´s maneuver does not only affect the liver as described above but also causes systemic changes as shown by Ypsilantis et al [27][28][29].…”
Section: Discussionmentioning
confidence: 94%
“…Many authors have demonstrated that the intermittent Pringle maneuver is safe and effective when used appropriately . However, this cross‐clamping technique blocks the mesenteric venous drainage and increases the pressure in the microvascular network of the intestine, which may induce bacterial translocation (BT) to the portal vein . Positive cultures of portal blood sampled following the Pringle maneuver have been reported in experimental studies but not in clinical studies .…”
Section: Introductionmentioning
confidence: 99%
“…However, this cross‐clamping technique blocks the mesenteric venous drainage and increases the pressure in the microvascular network of the intestine, which may induce bacterial translocation (BT) to the portal vein . Positive cultures of portal blood sampled following the Pringle maneuver have been reported in experimental studies but not in clinical studies . Thus, the reality of BT to the portal vein following the Pringle maneuver remains unclear in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Dello et al [9] found that total intermittent Pringle maneuver in patients undergoing liver resection is associated with a substantial increase in arterial intestinal fatty acid binding protein levels, which pointing to intestinal epithelial injury during liver surgery based on a research sample size of 24 patients. And Ypsilantiset al [10] reported that application of Pringle maneuver concurrently with extended liver radiofrequency ablation aggravated gut barrier dysfunction with more aggressive translocation of endotoxins and intestinal bacteria based on an animal model. Ischemiaereperfusion (I/R) injury after hepatectomy could be associated to GI injury too [11].…”
Section: Introductionmentioning
confidence: 99%
“…showed that of the intraoperative factors analyzed, anesthesia duration (285 10. AE 87.18 versus 247.73 AE 66.56 min, P < 0.001), operation duration (239.57 AE 82.66 versus 204.10 AE 63.42 min, P < 0.001), intraoperative estimated blood loss (300 [200, 800] versus 300 [200, 600] mL, P ¼ 0.014), crystalloids infusion (2200 [1700, 2700] versus 2175 [1700, 2600] mL, P ¼ 0.036), colloids infusion (1000 [1000, 1500] versus 1000 [500, 1500] mL, P ¼ 0.049), blood transfusion (0 [0, 400] versus 0 [0, 400] mL, P ¼ 0.050), urine output (500 [300, 800] versus 400 [200, 800] mL, P ¼ 0.047), and the use of Pringle maneuver (P ¼ 0.003) were statistically different between patients with and without postoperative GI complications.…”
mentioning
confidence: 99%